PENGASUHAN ORANG TUA ANAK PENYANDANG DISABILITAS INTELEKTUAL DI KELURAHAN WALITELON SELATAN KABUPATEN TEMANGGUNG - Hanifah Amalia Nur Janah; Bambang Sugeng; Benny Setia Nugraha (Peksos: Jurnal Ilmiah Pekerjaan Sosial, 2023)
This thesis examines parenting which refers to the attitude of parents in providing guidance, assistance, and care to children with intellectual disabilities. This research was conducted to examine more deeply the parenting of parents who have children with intellectual disabilities. It has the aim of obtaining an in-depth description of the characteristics of informants, parenting of children with intellectual disabilities with aspects of warmth, clarity of rules, level of expectation and communication. The method used is a qualitative approach in descriptive form and the techniques used are interviews, passive participatory observation, and documentation studies. The data sources in this study are six informants consisting of four parents of children with disabilities and two neighbors. Checking the validity of the data uses credibility through increased persistence, source triangulation, technical triangulation, time triangulation, and using reference materials. The results of this study indicate that both pairs of parent informants are fully aware of the child's condition well so that the child is given sufficient warmth, clarity of rules, level of expectation, and communication. This is according to the ability of parents even though they live in a deprived family. Parenting is considered good, it's just that there are obstacles or deficiencies in communication due to the intellectual disability experienced by the child. There are problems experienced by parents when caring for children with disabilities, namely difficulties for parents to understand children's rights and the low quality of communication between parents and children. Based on these problems, the researchers proposed a program that intends to solve this problem, namely "Increasing the Parenting Capacity of Children with Intellectual Disabilities".